Ureteral metastasis of a prostatic adenocarcinoma - Otta, Renan Javier; Gordillo, Carlos; Fernández, Inmaculada (Canadian Urological Association Journal, 2015)
The ureter is a rare location of metastasis for any kind of primary tumour. The first case of truly ureteral metastasis was described by Stow in 1909. Regarding prostatic metastasis, the frequency is much lower with only 43 cases reported in the last century. We present a case of an exceedingly rare ureteral metastasis of a prostatic adenocarcinoma. In spite of its low incidence, it should be considered in patients with ureteral obstruction and concurrent prostatic adenocarcinoma.